Corneal stromal microdots accumulation and its association with corneal neurodegeneration and retinal microvascular perfusion in diabetes - Wang, Jingrao; Wang, Shu; Zhang, Hong; Jin, Xin (Frontiers in Endocrinology, 2025)
PurposeThe purpose of the study was to investigate the deposition of microdots in corneal stroma in diabetes mellitus (DM) patients and assess the relationship between microdots and corneal nerve damage as well as retinal microvascular perfusion.Methods127 patients with DM and 36 age and sex-matched controls were included. All subjects were examined by in vivo confocal microscopy (IVCM) and optical coherence tomography angiography (OCTA). Histochemistry staining was also performed in cadaver corneas from patients with DM or control subjects.ResultsThe deposition of microdots was significantly increased in corneal stroma in patients with DM than controls (P<0.0001). Spearman’s rank correlation showed that the deposition of microdots in subepithelial, anterior stromal, mid stromal, posterior stromal, and pre-Descemet stromal layers had positive correlations with corneal nerve fiber density (CNFD) (q<0.0001, q<0.0001, q<0.0001, q=0.0039, and q=0.0104), corneal nerve fiber length (CNFL) (q<0.0001, q<0.0001, q<0.0001, q<0.0001, and q<0.0001), and corneal tortuosity (q<0.0001, q<0.0001, q<0.0001, q<0.0001, and q<0.0001). The subepithelial, anterior stromal, and mid stromal microdots also showed weak correlations with superficial vascular complexes (SVC) vessel density (VD) (q<0.0001, q=0.0011, and q=0.0004) and deep vascular complexes (DVC) VD (q=0.0001, q=0.0109, and q=0.0037). PAS and long Ziehl-Neelsen staining demonstrated lipofuscin deposits in cornea.ConclusionPatients with DM demonstrated a significant increase of deposition of microdots in corneal stroma which correlates with corneal nerve loss and retinal microvascular perfusion. Microdots are at least partially composed of lipofuscin which is also observed in corneal basal epithelial layer.